A Study of Tsirelson and Schreier Spaces - Ojha, Bhuwan Prasad; Sigdel, Dhruba Raj (Nepal Journal of Mathematical Sciences, 2022)
This paper is a short review of some results in Tsirelson space. The concept of the paper is to include some well-known theorems on Tsirelson’s space constructed by Figiel and Johnson together with results concerning holomorphic functions on the classical and modified mixed Tsirelson spaces.